Impossible (Food) Experiences in Extended Reality - Velasco, Carlos; Barbosa Escobar, Francisco; Petit, Olivia; Wang, Qian Janice (Frontiers in Computer Science, 2021)
We introduce a model to think about impossible experiences in mixed and virtual reality, while emphasizing the role of said experiences in the context of food. This reality-impossibility model includes two continua, namely, the reality-fantasy character of objects and environments, and the extent to which they follow the laws of physics-other laws. We present a series of examples in each of the quadrants of the model and discuss both the research possibilities and implications of impossible experiences.